Proposta de um programa interpretativo na Reserva Particular do Patrimônio Natural Estadual Mo’ã (Itaara, RS, Brasil) - Corrêa, Leticia Ramires (2019)
Faced with the challenge of getting humanity to understand its relation of interdependence with the natural environment, it is sought through a program and its instruments, such as guided trail and Interpretive Center, following the principles of Environmental Interpretation, revealing the nature of a attractive way to the visitor, in order to arouse their interest from the knowledge of the processes of nature and direct contact with it, so that it becomes interested in preserving it. In the search for the rapprochement of people with nature, Conservation Units allow environmental (re) interpretation in order to rediscover the meaning of nature in relation to the human. The MO'ã State Natural Heritage Private Reserve, located in Itaara / RS on the Plateau Ridge in the central region of Rio Grande do Sul, in the Core Zone of the Mata Atlântica Biosphere Reserve, is a Conservation Unit, which has the physical limit Arroio Manuel Alves, one of the natural heritage with greater potential for interpretation, as well as its other natural attributes of this area. On the way to the approach of the man of nature, this research proposes an interpretative program that aims to potentiate the conservation of the water resources in the State RPPN MO'Ã. We have the following specific objectives: a) To understand the river dynamics that occurs in the Arroio Manuel basin, in order to translate the processes and forms from the interpretative points. b) Define the activities to compose the Interpretative Program that instigates the visitor to think about the conservation of water resources. c) Discuss the contributions of the program to the sensitization of visitors. We emphasize the relevance of the Interpretative Program as an organized and planned instrument for translation and sensitization for the conservation of nature. In view of the proposed objectives, we used the methodological procedures, which were structured in stages: definition of the theoretical framework of investigation and survey of primary and secondary data; treatment and discussion of the data. As a result, we have composed the program 17 approaches of 8 subthemes referring to the central theme of the interpretative program which are the aspects of fluvial dynamics in the State RPPN MO'Ã. The program's proposal is made up of an Interpretive Center and a course with 8 stops for the environmental interpretation, using different techniques that are relevant to the visitor's sensibility to understand the processes and forms that are manifested in the landscape of the area, in order to that they feel motivated to conserve water resources through participation in the program. We conclude that the program contributes to the divulgation of the RPPN area as a space for contact with nature and the visitor's awareness for the conservation of water resources from an understanding of the forms and processes that occur in a river basin.